The Effect of Cognitive-Behavioral Therapy (CBT) on Shame and Self-Acceptance in Married Women with Depression - Mardi , Turan (Psychology of Woman Journal, 2025)
Objective: This study aimed to evaluate the effectiveness of Cognitive-Behavioral Therapy (CBT) in reducing feelings of shame and enhancing self-acceptance among married women with depression. Methods and Materials: The study employed a randomized controlled trial (RCT) design with a pre-test, post-test, and five-month follow-up. A total of 30 married women with depression from Tehran were randomly assigned to either the experimental group (n = 15), which received ten 90-minute CBT sessions, or the control group (n = 15), which did not receive any psychological intervention. The Experiences of Shame Scale (ESS) and the Self-Acceptance Questionnaire (SAQ) were used to assess the dependent variables at each assessment point. Data were analyzed using repeated measures ANOVA to examine changes over time, and Bonferroni post-hoc tests were conducted to determine specific group differences. Statistical analysis was performed using SPSS-27, with significance set at p < 0.05. Findings: The results indicated a significant main effect of time for both shame and self-acceptance. For shame, a significant reduction was observed across time points in the experimental group, F(2, 28) = 15.72, p = 0.002, η² = 0.47, with Bonferroni post-hoc tests revealing significant decreases from pre-test to post-test (p = 0.001) and pre-test to follow-up (p = 0.002). Similarly, self-acceptance scores significantly improved over time, F(2, 28) = 10.89, p = 0.005, η² = 0.39, with significant differences found between pre-test and post-test (p = 0.045), demonstrating the effectiveness of CBT in fostering self-acceptance. Conclusion: The findings suggest that CBT is an effective intervention for reducing shame and improving self-acceptance in married women with depression. These results highlight the importance of incorporating CBT techniques in therapeutic interventions to address emotional challenges associated with depression.